ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PADI DI DESA TAMBAKRIGADUNG KECAMATAN TIKUNG KABUPATEN LAMONGAN - Firmansah, Niken; Wardah (Jurnal Nirta : Inovasi Multidisiplin, 2025)
This study aims to analyze the factors that influence rice production in Tambakrigadung Village, Tikung District, Lamongan Regency. Rice production plays a crucial role in maintaining national food security. However, annual fluctuations in rice yields indicate the influence of various production factors. This research specifically examines the impact of seed quality, soil fertility, capital, technology, and labor on rice production. A quantitative approach was employed using purposive sampling, involving 50 rice farmers who own their land as respondents. Data were collected through questionnaires, interviews, observation, and documentation. The data were analyzed using a multiple linear regression model based on the Cobb-Douglas production function, with the assistance of SPSS software. The study aims to determine both the simultaneous and partial effects of each variable on rice production and to identify the nature of their relationships. The results are expected to serve as a basis for formulating strategies to enhance agricultural productivity at the village level. This research is intended to contribute to farmers, local governments, and stakeholders in developing productive and sustainable agricultural practices.